Devolution in Kenya: Derailed or on track?. Issue 4 (2nd October 2015) - Steeves, Jeffrey
Abstract : The 2010 Kenya Constitution introduced a new level of government through a process of devolution. County governments were established in each of 47 districts with elected Governors and Members of County Assemblies, and each government acquired their own Executive Council and public service. From independence forward Kenya had been a highly centralised polity reinforced by the rise of an imperial presidency. Now the political system has been turned on its head. How will the national political and administrative elites react to this veritable revolution? Will devolution succeed? Key variables will be used to assess Kenya's early devolution experiment.